Cardiovascular toxicity profiles of immune checkpoint inhibitors with or without angiogenesis inhibitors: a real-world pharmacovigilance analysis based on the FAERS database from 2014 to 2022 - Wang, Yanfeng; Cui, Chanjuan; Deng, Lei; Wang, Lin; Ren, Xiayang (Frontiers in Immunology, 2023)
Background Immune checkpoint inhibitors (ICIs) combined with angiogenesis inhibitors (AGIs) have become increasingly available for multiple types of cancers, although the cardiovascular safety profiles of this combination therapy in real-world settings have not been elucidated to date. Therefore, we aimed to comprehensively investigate the cardiovascular toxicity profiles of ICIs combined with AGIs in comparison with ICIs alone. Methods The Food and Drug Administration Adverse Event Reporting System (FAERS) database from the 1st quarter of 2014 to the 1st quarter of 2022 was retrospectively queried to extract reports of cardiovascular adverse events (AEs) associated with ICIs alone, AGIs alone and combination therapy. To perform disproportionality analysis, the reporting odds ratios (RORs) and information components (ICs) were calculated with statistical shrinkage transformation formulas and a lower limit of the 95% confidence interval (CI) for ROR (ROR025) > 1 or IC (IC025) > 0 with at least 3 reports was considered statistically significant. Results A total of 18 854 cardiovascular AE cases/26 059 reports for ICIs alone, 47 168 cases/67 595 reports for AGIs alone, and 3 978 cases/5 263 reports for combination therapy were extracted. Compared to the entire database of patients without AGIs or ICIs, cardiovascular AEs were overreported in patients with combination therapy (IC025/ROR025 = 0.559/1.478), showing stronger signal strength than those taking ICIs alone (IC025/ROR025 = 0.118/1.086) or AGIs alone (IC025/ROR025 = 0.323/1.252). Importantly, compared with ICIs alone, combination therapy showed a decrease in signal strength for noninfectious myocarditis/pericarditis (IC025/ROR025 = 1.142/2.216 vs. IC025/ROR025 = 0.673/1.614), while an increase in signal value for embolic and thrombotic events (IC025/ROR025 = 0.147/1.111 vs. IC025/ROR025 = 0.591/1.519). For outcomes of cardiovascular AEs, the frequency of death and life-threatening AEs was lower for combination therapy than ICIs alone in noninfectious myocarditis/pericarditis (37.7% vs. 49.2%) as well as in embolic and thrombotic events (29.9% vs. 39.6%). Analysis among indications of cancer showed similar findings. Conclusion Overall, ICIs combined with AGIs showed a greater risk of cardiovascular AEs than ICIs alone, mainly due to an increase in embolic and thrombotic events while a decrease in noninfectious myocarditis/pericarditis. In addition, compared with ICIs alone, combination therapy presented a lower frequency of death and life-threatening in noninfectious myocarditis/pericarditis and embolic and thrombotic events.